2019
DOI: 10.1042/bsr20181122
|View full text |Cite
|
Sign up to set email alerts
|

2,5-Hexanedione mediates neuronal apoptosis through suppression of NGF via PI3K/Akt signaling in the rat sciatic nerve

Abstract: Because precise mechanism for 2,5-hexanedione (HD)-induced neuronal apoptosis largely remains unknown, we explored the potential mechanisms both in vivo and in vitro. Rats were intraperitoneally exposed to HD at different doses for 5 weeks, following which the expression levels of nerve growth factor (NGF), phosphorylation of Akt and Bad, dimerization of Bad and Bcl-xL, as well as the release of cytochrome c and the caspase-3 activity were measured. Moreover, these variables were also examined in vitro in HD-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Studies have also proven that activation of the proNGF/p75NTR pathway in cerebral cortical neurons is closely related to JNK activation and regulates JNK pathway-induced apoptosis to modulate levels of the c-Jun kinase-dependent proteins Bax and Bcl-2 [ 42 , 43 ]. In this study, we found that HD promoted JNK phosphorylation and changed the levels of the JNK downstream apoptosis-related proteins Bax and Bcl-2 in spinal cord tissues and VSC4.1 cells, consistent with previous reports [ 44 ]. In addition, inhibition of JNK activation significantly reduced HD-induced apoptosis and reversed activation of Bax and Bcl-2 in vitro .…”
Section: Discussionsupporting
confidence: 93%
“…Studies have also proven that activation of the proNGF/p75NTR pathway in cerebral cortical neurons is closely related to JNK activation and regulates JNK pathway-induced apoptosis to modulate levels of the c-Jun kinase-dependent proteins Bax and Bcl-2 [ 42 , 43 ]. In this study, we found that HD promoted JNK phosphorylation and changed the levels of the JNK downstream apoptosis-related proteins Bax and Bcl-2 in spinal cord tissues and VSC4.1 cells, consistent with previous reports [ 44 ]. In addition, inhibition of JNK activation significantly reduced HD-induced apoptosis and reversed activation of Bax and Bcl-2 in vitro .…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, the induction of p-mTOR is closely related to tumor invasion, tumor stage and low survival [ 45 ]. To further verify our conclusion, PI3K pathway inhibitor LY294002 and PI3K pathway activator IGF-1 were used in the study to further block or strengthen the PI3K pathway as previously described [ 46 , 47 ].The effects of high-dose LQ on the signal pathway, autophagy and apoptosis were all enhanced by LY294002 and were counteracted by the addition of IGF-1. Thus, we conjecture that LQ exerted anti-tumor effects through inactivating the PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…NGF plays a key role in promoting the growth and development of the nervous system. NGF can protect the neurons from further damage in the already impaired nervous system, promotes the regeneration of nerve fibers and axons, improves nerve conduction function, and relieves neuropathic pain by restoring the integrity of the myelin sheath [ 46 ]. Preclinical studies have shown that levels of NGF are increased in preclinical models of inflammation and peripheral nerve injury [ 47 ].…”
Section: Discussionmentioning
confidence: 99%